MAGNETIC INVESTIGATION OF AN UNUSUAL DISSYMMETRIC BINUCLEAR MANGANESE CARBOXYLATE COMPLEX - Ghenadie Novitchi; Jean-Pierre Costes; Lilia Popovschi; Sergiu Shova; Aurelian Gulea (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2006)
The magnetic susceptibility (χT) of an unusual dissymmetric binuclear manganese corboxylate complex has been measured from 2 to 300K. The magnetic data which have been fitted with help of the Heisenberg Dirac Van Vleck HDVV spin-exchange Hamiltonian H = − J S 1 S 2 , indicate that an antiferromagnetic interaction equal to J = -0.90(1) cm-1 is present. A correlation between J values and Mn-H2O-Mn angles has been tempted.